Congenital Aniridia: Clinical Features and Therapeutic Approaches (Case Report) - N. Yu. Yusef; N. V. Мakashova; A. E. Vasillyeva; Kh. Alhumidi; I. A. Ronzina (Oftalʹmologiâ)
A clinical case of congenital aniridia in combination with high degree hyperopia, congenital cataract, ophthalmohypertension, foveal hypoplasia is presented. The article analyzes the results of a complex of morphofunctional studies conducted before and after cataract surgery, presents practical data on the differential diagnosis of glaucoma and ophthalmohypertension and analyzes therapeutic approaches, including the use of a diaphragm contact lens and a three-component tear substitute Stillavit.